Kontribusi Fintech atas Perkembangan Fan Realita UMKM di Indonesia - Sumarni, Rohita Nofa Linda (Universitas Muhammadiyah Surakarta, 2025)
The development of technology is currently growing rapidly and quickly, this era of globalization affects people's behavior in carrying out daily activities. Current technology has an impact on the economic aspect with the emergence of fintech as a breakthrough in the era of globalization in easy access to finance. Fintech also gave rise to fintch as a breakthrough for making payments when making transactions. Fintech and QRIS have an impact on MSME business actors in developing their businesses. Fintech makes it easy for UMKM business actors to take out business capital loans to develop their businesses. While QRIS provides convenience when making transactions and guarantees security when making transactions. With QRIS, UMKM actors are not worried about the circulation of counterfeit money, and provides a financial analysis to evaluate their business. Business actors are asked to increase financial literacy with the development of technology, business actors must be able to improve their skills in order to compete with large businesses.